2019
DOI: 10.3389/fpsyg.2019.02712
|View full text |Cite|
|
Sign up to set email alerts
|

Performance Indicators in Young Elite Beach Volleyball Players

Abstract: The aim of this study was to analyze tactical and technical behavior across different ages and genders in young, elite beach volleyball players. Methods: Forty teams from the Under-18, Under-20, Under-21, and Under-22 from semifinals and finals of the 2016 World Championships and the 2016 European Championship were analyzed. The sample was composed of 69 sets. The variables studied included: Rally time, set time, match time, serve efficacy (standing serve, floating serve, and jump serve), setting efficacy (for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Notational analysis is the process of recording, treatment, and diagnostics of events taking place in a competition (Drust, 2010). Several studies have been conducted on the notational analysis of technical and tactical aspects of volleyball (Ciuffarella et al, 2013) and beach volleyball (Jimenez-Olmedo, Penichet-Tomas, Saiz-Colomina, Martinez-Carbonell, & Jove-Tossi, 2012;Koch & Tilp, 2009b;Pérez-Turpin et al, 2019;Tilp, Koch, Stifter, & Ruppert, 2006). It has facilitated coaches in the analysis of movement patterns, strategy, and tactics of the individual player as well as the team's performance.…”
Section: Introductionmentioning
confidence: 99%
“…Notational analysis is the process of recording, treatment, and diagnostics of events taking place in a competition (Drust, 2010). Several studies have been conducted on the notational analysis of technical and tactical aspects of volleyball (Ciuffarella et al, 2013) and beach volleyball (Jimenez-Olmedo, Penichet-Tomas, Saiz-Colomina, Martinez-Carbonell, & Jove-Tossi, 2012;Koch & Tilp, 2009b;Pérez-Turpin et al, 2019;Tilp, Koch, Stifter, & Ruppert, 2006). It has facilitated coaches in the analysis of movement patterns, strategy, and tactics of the individual player as well as the team's performance.…”
Section: Introductionmentioning
confidence: 99%
“…33 Despite the better performance in spike with alternative techniques, beach volleyball is also dependent upon a multitude of variables that affect the outcome of the game, such as serve reception, setting, blocking, serving, accuracy of shots in attack and other personal abilities of the players. 43 Furthermore, the outdoor conditions (e.g., depth of sand, speed of wind) often make it difficult for players to use the same technique in spike. In a recent study, 38 it was revealed that there were no differences regarding performance between players using the various arm swing techniques in elite beach volleyball.…”
Section: Discussionmentioning
confidence: 99%
“…Physically it is demanding, with 50-minute matches and defensive and offensive actions with short and explosive execution times of 3 to 4 seconds (anaerobic) (Pérez, 2021). Therefore, technical gestures such as jumping take a relevant role (Bosco & Rusko, 1983;Billington, 2012;Pezoa Fuentes, 2018;Nasuka, 2019), blocking (Bardales, 2014) and serving and of the temporal variables of the game related to essential aspects such as biodynamics and tactics (Clavijo-Redondo et al, 2016;Pérez-Turpin et al, 2019;Petrovici & Kovacs, 2021); because of the above, athletes should be in optimal physical and technical-tactical conditions to cope with the demands required by the sport (Pérez, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Body analysis and control is essential for training and performance development (López et al, 2019), therefore, such controls should be developed from anthropometric and body composition analysis as fundamental elements to follow-up and adjust training (Lentini et al, 2006). Such analysis is important because it helps to define the morphological features of athletes (Barajas et al, 2021), providing information not only of the physical conditions but also of their potential performance in relation to the function they have during the game (Pérez-Turpin et al, 2019;Gualdi & Zaccagni, 2001), in this sense, a characteristic morphological feature of the beach and indoor volleyball player of high competition is the height (D´Anastasio et al, 2019), as well as the lengths of upper and lower limbs, i.e., a tall player with elongated limbs, has a greater chance of success due to its ease to perform serves, spikes and blocks (Nasuka, 2019), jumping and block jump reach is influenced by arms and legs length, so absolute height contributes significantly to the percentage of total variance associated with athletic success (De Farias et al, 2016). It should also be considered that anthropometric data allow coaches to create normative standards for sports level, identify talents and design to optimize sports performance (Sánchez Muñoz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%